Production of xylooligosaccharides and fermentable sugars from oil palm mesocarp fiber by subcritical H₂O - CO₂ pretreatment - Ahmad, Norlailiza (2018)
Oil palm mesocarp fiber (OPMF) generated from oil palm processing is available abundantly and improper handling of OPMF has lead to serious pollution. High content of carbohydrate polymer in OPMF serves as feedstock for fermentable sugars production with appropriate pretreatments. The present works aimed to investigate xylooligosaccharide (XOs) and fermentable sugar production from OPMF in subcritical H2O-CO2 pretreatment at a temperature range of 150- 200°C and 20-60 min with pressure vary from 3-5 MPa. The pretreated solids and liquids from this process were separated by filtration and characterized. XOs, monomeric sugars, acids, furans and phenols in pretreated liquids were analyzed by using HPLC. XOs with a degree of polymerization DP X2-X4 which is xylobiose, xylotriose, xylotetraose were analysed by using HPAECPAD. Enzymatic hydrolysis was performed on cellulose-rich pretreated solids to study the xylose and glucose production. Morphological changes of pretreated solids were analyzed by SEM, WAXD and BET surface area. An optimal condition for XOs production was obtained at 180°C, 60 min, 3 MPa with a concentration of 81.60 mg/g which corresponded to 36.59% of XOs yield from xylan. On the other hand, the highest xylose and glucose yields obtained from conversion of hemicellulose and cellulose were 29.96% and 84.65%, respectively at cellulase loadings of 10 FPU/g-substrate. The results obtained clearly indicated that OPMF was a potential material for XOs and fermentable sugar production using subcritical H2O-CO2 method.